Sustainability issues in the student business incubators program - Amizuar, Sabilil Hakimi; Setiadi, Rezky Mehta; Suryahadikusumah, Ahmad Rofi (Privietlab, 2026)
The success of a business incubator is not only measured by the number of business groups born, but also by the ability of the business to survive, adapt, and grow sustainably in the midst of market dynamics. This study aims to provide a comprehensive understanding of the factors that affect the sustainability of student startups through university-owned business incubators. The Systematic Literature Review (SLR) method was used to examine sustainability issues in student business incubators, with the following inclusion criteria: 1) articles edited by SINTA and Scopus, 2) publication period 2014–2024, 3) focus on the context of business incubators in higher education, and 4) evaluation results of the business incubator program. The results of the study show that student business sustainability needs to be supported by business incubators with 1) social orientation and non-commercial added value, 2) strengthening the business ecosystem, mentoring, and digitalization, 3) sustainable knowledge transfer, and 4) institutional support in downstream innovation strategies.